2014
DOI: 10.1037/a0035960
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation of respiratory sinus arrhythmia in adult romantic partners.

Abstract: Questions surrounding physiological interdependence in romantic relationships are gaining increased attention in the research literature. One specific form of interdependence, coregulation, can be defined as the bidirectional linkage of oscillating signals within optimal bounds. Conceptual and theoretical work suggests that physiological coregulation should be instantiated in romantic couples. Although these ideas are appealing, the central tenets of most coregulatory models await empirical evaluation. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(166 citation statements)
references
References 59 publications
9
155
2
Order By: Relevance
“…Typically, these measures were obtained through self-report questionnaires or behavioral coding. Out of 17 tests, 13 significant (e.g., Hasler & Troxel, 2010; Helm et al, 2012, 2014; Hubler, 2013; Levenson & Gottman, 1983; Liu et al, 2013; Saxbe & Repetti, 2010; Schneiderman et al, 2014) and 4 non-significant effects (Levenson & Gottman, 1985; Reed et al, 2013; Sauder, 2001; Thomsen & Gilbert, 1998) were reported. Positive associations in cortisol were linked to poorer relationship quality in daily life (Liu et al, 2013; Saxbe & Repetti, 2010) and during laboratory-based conflict (Schneiderman et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, these measures were obtained through self-report questionnaires or behavioral coding. Out of 17 tests, 13 significant (e.g., Hasler & Troxel, 2010; Helm et al, 2012, 2014; Hubler, 2013; Levenson & Gottman, 1983; Liu et al, 2013; Saxbe & Repetti, 2010; Schneiderman et al, 2014) and 4 non-significant effects (Levenson & Gottman, 1985; Reed et al, 2013; Sauder, 2001; Thomsen & Gilbert, 1998) were reported. Positive associations in cortisol were linked to poorer relationship quality in daily life (Liu et al, 2013; Saxbe & Repetti, 2010) and during laboratory-based conflict (Schneiderman et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, known as physiological linkage, synchrony, or coregulation, is defined as covariation between two people in their physiological states. Although documented as early as the 1950s in client-therapist dyads (Di Mascio, Boyd, Greenblat, & Solomon, 1955), interest in physiological linkage, especially in romantic couples, has been increasing in the past few years (Helm, Sbarra, & Ferrer, 2012, 2014; Liu, Rovine, Cousino Klein, Almeida, 2013; Papp, Pendry, Simon, & Adam, 2013; Saxbe et al, 2014; Saxbe & Repetti, 2010). The advent of more sophisticated technological and quantitative techniques for capturing dynamic inter-individual physiological processes (Ferrer & Helm, 2013; McAssey, Helm, Hsieh, Sbarra, & Ferrer, 2013; Poh, Swensen, & Picard, 2010) has primed the field for continuing advances.…”
mentioning
confidence: 99%
“…First, some techniques consider the relationship between two people's physiology at the same time point (e.g., Papp, Pendry, Simon, & Adam, 2013;Saxbe & Repetti, 2010;Waters et al, 2014), which is important for examining shared experiences. Other techniques use a time-lagged design to examine whether one partner's physiology at one time point predicts the other partner's physiology at a later time point (e.g., Helm et al, 2014;Kraus & Mendes, 2014;Liu, Rovine, Klein, & Almeida, 2013), which is important for examining whether one partner's physiological state is predicted by the other partner's state.…”
Section: Statesmentioning
confidence: 99%
“…The authors speculated that this process was one potential manifestation of human coregulation (see Sbarra & Hazan, 2008), but, to date, there is no evidence that coregulation itself has any direct relevance for health. Part of the problem with the Helm et al (2014) finding is that HRV, as an outcome variable, is not calibrated in a meaningful way that allows for a direct understanding of the potential health relevance of the findings.…”
Section: Moving Forward: Empirical Examples For Studying Relationshipmentioning
confidence: 99%